Flexible strain sensor and preparation method thereof
By dispensing and printing parallelly arranged conductive patterns on the pre-stretched polymer substrate, a pattern-type flexible strain sensor was prepared, which solved the problems of uncontrollability and poor stability of traditional crack-type sensors, and achieved high Sensitivity and sensor performance over a wide strain range.
Patent Information
- Application Number
- CN202411593881.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-08
AI Technical Summary
The existing crack-type flexible strain sensors have strong uncontrollability during the preparation process, poor sensing stability, and it is difficult to maintain reliability in a long-term use environment.
Pre-stretch-dispensing printing method is used to prepare flexible strain sensors, and parallelly arranged conductive patterns are printed on the pre-stretched polymer substrate to form a pattern-type structure, and the conductive paths are used during stretching and retraction. Contact and separation enable highly sensitive strain sensing.
It realizes sensing performance with high sensitivity, wide strain range and excellent stability, solving the problem of insufficient reliability and preparation controllability of traditional crack-type strain sensors.
Smart Images

Figure CN119468896A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a flexible sensor, and in particular to a flexible strain sensor and a preparation method thereof. Background Art
[0002] Flexible strain sensors are based on flexible polymers. Their stretchable and bendable properties allow them to conform to human skin and are widely used in various human-computer interaction fields, such as virtual reality (VR), sign language recognition, robot control, rehabilitation equipment, etc. How to accurately capture and quantify the weak deformation signals on the human body surface poses challenges to the various performances of flexible strain sensors, including sensitivity, detection limit, stability, and repeatability, to ensure that the tiny strains at the wearing position can be truly and accurately measured. Highly sensitive and robust flexible strain sensors have potential market value and important research significance in many fields such as daily life, medical health, and industrial production.
[0003] At present, in order to achieve highly sensitive strain sensing, the mainstream design is a resistive strain sensor based on a crack sensing mechanism. Its structure is generally composed of two parts: one is a stretchable and bendable flexible polymer substrate that plays a supporting role, which has sufficient mechanical strength and flexibility to meet basic wearing requirements, and the other is a conductive material film layer that plays a sensing function, which feeds back the strain change as a resistance change of the layer to achieve the strain sensing function. The crack-type strain sensor introduces micro / nanocracks in the conductive active layer by bending and stretching the flexible polymer matrix. When the device is strained, the generation of these micro / nano channel cracks leads to a steep resistance response, quantifying the strain as a resistance change to achieve the correspondence between mechanical quantity and electrical quantity, and realizing highly sensitive strain sensing.
[0004] Although the sensitivity of crack-type strain sensors has been significantly improved, they face the problems of crack recoverability and poor reliability. Since the crack formation process is random and uncontrollable, the consistency and repeatability of the preparation process are difficult to guarantee, which poses a challenge to the reliability in long-term use environments. New structural designs are needed to balance the electrical sensitivity and mechanical durability of flexible strain sensors.
[0005] It should be noted that the information disclosed in the above background technology section is only used for understanding the background of the present application, and therefore may include information that does not constitute prior art known to ordinary technicians in the field. Summary of the invention
[0006] The main purpose of the present invention is to overcome the defects existing in the above-mentioned background technology and provide a flexible strain sensor and a preparation method thereof.
[0007] To achieve the above object, the present invention adopts the following technical solutions:
[0008] A flexible strain sensor, comprising:
[0009] A polymer substrate, wherein the polymer substrate is composed of a copolymer P(MEA-co-BA) of 2-methoxyethyl acrylate (MEA) and 2-butyl acrylate (BA), and a silver nanowire (AgNWs) network is embedded on the surface;
[0010] A conductive pattern, wherein the conductive pattern is printed on a pre-stretched polymer substrate by dispensing to form a parallel pattern structure;
[0011] A chemical reduction gold plating layer is formed on the conductive pattern to improve contact resistance and enhance sensor stability;
[0012] The gold-plated polyimide (PI) film is connected to the conductive pattern as a conductor to transmit electrical signals.
[0013] Further:
[0014] After pre-stretching and retraction, the spacing between adjacent printed patterns is no more than 20 μm, the length of the parallel lines is 1-3 mm, and the number of parallel lines is 25-60.
[0015] A method for preparing a flexible strain sensor comprises the following steps:
[0016] S1, preparing a polymer substrate composed of a copolymer of 2-methoxyethyl acrylate (MEA) and 2-butyl acrylate (BA) P(MEA-co-BA), and embedding a silver nanowire (AgNWs) network on the surface;
[0017] S2, pre-stretching the polymer substrate to a predetermined degree and fixing it;
[0018] S3, printing a conductive pattern on a pre-stretched polymer substrate by dispensing to form a parallel pattern structure;
[0019] S4, performing chemical reduction gold plating on the conductive pattern to improve contact resistance and enhance sensor stability;
[0020] S5. Connect the conductive pattern to the gold-plated polyimide (PI) film to form a conductive connection for transmitting electrical signals.
[0021] Further, step S1 includes preparing a glass interlayer coated with silver nanowires (AgNWs), specifically comprising:
[0022] Add silver nanowire (AgNWs) ethanol dispersion dropwise onto a glass slide and evenly wet the entire surface of the glass slide; place the treated glass slide on a horizontally placed heating plate and heat and dry it for later use;
[0023] After the surface of another glass slide was treated in an oxygen plasma cleaning machine, a dextran (molecular weight 40,000) aqueous solution was spin-coated and the residual water was evaporated by heating to form a water-soluble sacrificial layer.
[0024] Furthermore, in step S1, the preparation of the polymer substrate specifically includes:
[0025] 2-Methoxyethyl acrylate (MEA) and 2-butyl acrylate (BA) were mixed at a molar ratio of 1:1;
[0026] Add 0.1% polyethylene glycol diacrylate (PEGDA) relative to the total molar amount of MEA and BA;
[0027] Add 1% 1-hydroxycyclohexylphenyl ketone (photoinitiator 184) relative to the total molar amount of MEA and BA;
[0028] 0.1–2 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) was added as an ionic liquid to enhance the conductivity of the polymer;
[0029] The resulting mixture was injected into a glass slide sandwich coated with an AgNWs layer and photo-initiated polymerization was achieved by ultraviolet light irradiation.
[0030] Further, in step S2, the polymer substrate is pre-stretched to a length of 140%-200%.
[0031] Furthermore, in step S3, the conductive ink used for dispensing printing includes the following components: hydroxyl-terminated polydimethylsiloxane PDMS-OH; octamethylcyclotetrasiloxane D4; crosslinking agent 3-(2,3-epoxypropyloxy)propyltrimethoxysilane (GPTMS); silver microflake powder; and dibutyltin dilaurate (DBTDL) as a catalyst.
[0032] Furthermore, in step S3, the length of the parallel lines printed by glue dispensing is 1-3mm, the lateral arrangement period is 0.85mm, the number of parallel lines is 25-60, the height of glue dispensing printing is 0.2-0.4mm, and the printing speed is 20-30mm / min to ensure that adjacent patterns can contact after pre-stretching is released, and are heated at 70°C for more than 30 minutes after printing to cure; the spacing between adjacent printed patterns after pre-stretching and retraction is not greater than 20μm.
[0033] Furthermore, in step S4, the gold plating solution used in the chemical reduction gold plating contains HAuCl4, Na2S2O3 and Na2SO3.
[0034] Furthermore, in step S4, the sample is immersed in the solution and reacted at 70° C. for 2 hours.
[0035] The present invention has the following beneficial effects:
[0036] The present invention proposes a flexible strain sensor and a preparation method thereof. A pattern-type strain sensor is constructed based on a pre-stretching-dispensing printing conductive pattern, and highly sensitive strain sensing is achieved by utilizing the contact and separation of the conductive path during stretching and retraction. The sensing mechanism does not involve the destruction and reconstruction of the conductive path, and can effectively solve the problem of poor reliability of crack-type strain sensing. It exhibits stable and reliable sensing performance in cyclic tests.
[0037] In order to solve the problems of insufficient controllability and poor sensing stability in the preparation of crack-type flexible strain sensors, the preparation method of the present invention prepares a pattern-type flexible strain sensor by pre-stretching-dispensing printing of a conductive pattern, prints a parallel conductive pattern similar to micro / nanocracks on a pre-stretched polymer substrate, effectively converts uncontrollable micro / nanocracks into gaps between adjacent conductive paths, and utilizes the contact and separation of the conductive paths during stretching and retraction to achieve high-sensitivity strain sensing. The sensing mechanism does not involve the random generation of cracks and the unstable recovery of the conductive path, and can effectively solve the problems of poor reliability and uncontrollable preparation of crack-type strain sensors.
[0038] The present invention prints parallel arranged conductive patterns on a pre-stretched polymer substrate by dispensing, and obtains a patterned flexible strain sensor after release. The prepared strain sensor has excellent sensing performance with high sensitivity, wide strain range and excellent stability.
[0039] Other beneficial effects of the embodiments of the present invention will be further described below. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 Flow chart of a method for preparing a flexible strain sensor according to an embodiment of the present invention.
[0041] Figure 2 This is a schematic diagram of the structure of a polymer film with an AgNWs network embedded on its surface prepared by a sandwich method according to an embodiment of the present invention.
[0042] Figure 3 This is a sample image after pre-stretching fixed glue printing according to an embodiment of the present invention.
[0043] Figure 4 This is a sample picture stored on release paper after chemical reduction gold plating according to an embodiment of the present invention.
[0044] Figure 5 This is a microscopic morphology diagram of the flexible strain sensor according to an embodiment of the present invention.
[0045] Figure 6 Graph showing the strain response curve and cyclic stability test data of the flexible strain sensor according to an embodiment of the present invention. DETAILED DESCRIPTION
[0046] The following is a detailed description of the embodiments of the present invention. It should be emphasized that the following description is only exemplary and is not intended to limit the scope and application of the present invention.
[0047] It should be noted that when an element is referred to as being "fixed to" or "disposed on" another element, it can be directly on the other element or indirectly on the other element. When an element is referred to as being "connected to" another element, it can be directly connected to the other element or indirectly connected to the other element. In addition, connection can be used for fixing as well as for coupling or communication.
[0048] It should be understood that the orientation or position relationship indicated by terms such as "length", "width", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside" and "outside" are based on the orientation or position relationship shown in the accompanying drawings, and are only for the convenience of describing the embodiments of the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.
[0049] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the embodiments of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0050] See also Figures 1 to 5 An embodiment of the present invention provides a flexible strain sensor, comprising: a polymer substrate 1, wherein the polymer substrate 1 is composed of a copolymer P (MEA-co-BA) of 2-methoxyethyl acrylate (MEA) and 2-butyl acrylate (BA), and a silver nanowire (AgNWs) network is embedded on the surface; a conductive pattern 2, wherein the conductive pattern 2 is printed on the pre-stretched polymer substrate 1 by dispensing to form a parallel pattern structure; a chemical reduction gold-plated layer 3, covering the conductive pattern 2 to improve contact resistance and enhance sensor stability; a gold-plated polyimide (PI) film 4, connected to the conductive pattern 2 as a wire for transmitting electrical signals.
[0051] In a preferred embodiment, after pre-stretching and retraction, the spacing between adjacent printed patterns is no more than 20 μm, the length of the parallel lines is 1-3 mm, and the number of parallel lines is 25-60.
[0052] See also Figures 1 to 5 The present invention also provides a method for preparing a flexible strain sensor, comprising the following steps:
[0053] Step S1, preparing a polymer substrate 1, which is composed of a copolymer P(MEA-co-BA) of 2-methoxyethyl acrylate (MEA) and 2-butyl acrylate (BA), and embedding a silver nanowire (AgNWs) network on the surface;
[0054] Step S2, pre-stretching the polymer substrate 1 to a predetermined degree and fixing it;
[0055] Step S3, printing the conductive pattern 2 on the pre-stretched polymer substrate 1 by dispensing to form a parallel pattern structure;
[0056] Step S4, performing chemical reduction gold plating on the conductive pattern 2 to improve contact resistance and enhance sensor stability;
[0057] Step S5, connecting the conductive pattern to the gold-plated polyimide (PI) film 4 to form a conductive connection for transmitting electrical signals.
[0058] The present invention provides a flexible strain sensor with high sensitivity, high stability and strong controllability and a preparation method thereof. The sensor uses P (MEA-co-BA) copolymer as a substrate material, and a silver nanowire network is embedded on the surface. A parallel conductive pattern is formed by pre-stretching and dispensing printing technology, which is effectively converted into a controllable pattern path, replacing the uncontrollable crack path in the traditional crack-type strain sensor. This design not only improves the controllability and consistency of the sensor preparation, but also improves the contact resistance and enhances the stability of the sensor through chemical reduction gold plating technology. In addition, while maintaining high sensitivity, the sensor of the present invention also realizes sensing in a wide strain range, breaking through the limitation that the conductive circuit of the traditional crack-type sensor is easily destroyed within a small strain range, thereby showing stable and reliable sensing performance in the cycle test, meeting the needs of daily life, medical health, industrial production and other fields for highly sensitive and robust flexible strain sensors.
[0059] The specific embodiments of the present invention are further described below.
[0060] In the embodiment of the present invention, a pattern-type flexible strain sensor is obtained by dispensing and printing a parallel conductive pattern on a pre-stretched polymer substrate, and then releasing the pattern-type flexible strain sensor. The preparation process of the flexible strain sensor includes several important steps such as transferring the AgNWs layer, pre-stretching fixation and dispensing printing, and chemical reduction gold plating process. The prepared strain sensor has excellent sensing performance with high sensitivity, wide strain range and excellent stability.
[0061] The process of preparing the flexible strain sensor is as follows Figure 1 As shown, the specific steps are as follows:
[0062] ① Drop coating of AgNWs layer on glass substrate
[0063] A glass slide was used as the glass substrate. First, the slide was placed in an oxygen plasma cleaner for about 3 minutes, and then 1 ml of 5 mg / ml silver nanowire (AgNWs) ethanol dispersion was added to each slide to evenly wet the entire surface of the slide. The slide was then placed on a horizontal heating plate and heated to 60°C for drying.
[0064] ②Polymer transfer AgNWs layer
[0065] The AgNWs layer on the glass slide was transferred to the polymer surface by photopolymerization using the sandwich method, e.g. Figure 2 As shown, one of the two glass slides used as the interlayer is obtained by step ①, and the other glass slide needs to be attached with a water-soluble sacrificial layer on the surface to facilitate subsequent peeling. After the glass slide is placed in an oxygen plasma cleaning machine for about 3 minutes, a dextran (molecular weight 40,000) aqueous solution with a mass fraction of about 8% is spin-coated. The spin-coating parameters are first 500 rpm for 5 seconds and then accelerated to 1500 rpm for 20 seconds, and the residual water is heated to evaporate. The polymer monomer is injected into the interlayer of the two parallel glass slides using a syringe and photo-initiated polymerization. The thickness of the interlayer is determined by the thickness of the 3M double-sided tape. Considering the mechanical strength requirements of the polymer, the thickness should not be less than 0.25 mm.
[0066] The polymer selected was a copolymer of 2-methoxyethyl acrylate (MEA) and 2-butyl acrylate (BA), P(MEA-co-BA), and the viscosity and tensile resilience of the flexible polymer substrate were used for subsequent pre-stretching and dispensing printing. MEA and BA were mixed evenly at a molar ratio of 1:1, and 0.1% of polyethylene glycol diacrylate (PEGDA, average molecular weight 400) and 1% of 1-hydroxycyclohexyl phenyl ketone (photoinitiator 184) were added relative to the total molar amount, and 0.1-2M lithium bistrifluoromethanesulfonyl imide (LiTFSI) was added to dissolve. After mixing evenly, it was injected into the glass slide interlayer and exposed to ultraviolet light for 1 hour before being taken out. The edge was pried open underwater with the help of the dissolution of dextran to achieve peeling, and a P(MEA-co-BA) polymer film with an AgNWs network embedded on the surface was obtained. LiTFSI is added as an ionic liquid, so that the obtained P(MEA-co-BA) polymer acts as an ionic conductor and still has conductivity under large strain conditions.
[0067] ③Pre-stretching and fixing of polymer substrate
[0068] Use scissors to cut off the 3M double-sided tape around the P(MEA-co-BA) polymer film, as well as the part of incomplete polymerization caused by monomer evaporation near the injection port. After the P(MEA-co-BA) polymer film with AgNWs embedded on the surface is stretched horizontally to 140%-200% of the length, the back side (the side without AgNWs) of P(MEA-co-BA) is fixed on the glass slide by the viscosity of the polymer film itself. A water-soluble sacrificial layer needs to be attached to the surface of the glass slide as described in step ② to facilitate subsequent separation.
[0069] ④Glue printing
[0070] The electrode pattern was printed by a high-viscosity dispensing printer. The printing ink was the PDMS-OH / Ag conductive ink configured in this scheme. This was because the commercial conductive silver paste had poor bonding strength with the polymer film, which would cause the conductive pattern to separate from the polymer and fall off when the polymer substrate was released from the pre-stretched state to its original length. The configuration method of the conductive ink was as follows: 0.3g of hydroxyl-terminated polydimethylsiloxane PDMS-OH (average molecular weight 110,000), 0.7ml of octamethylcyclotetrasiloxane D4, and 19μl of crosslinker 3-(2,3-epoxypropyloxy)propyltrimethoxysilane (GPTMS) were mixed evenly under magnetic stirring, 3.9g of silver micro-flake powder with an average particle size of 2μm was added, and magnetic stirring was performed for 24h to mix evenly. Finally, 1μl of dibutyltin dilaurate (DBTDL) was added as a catalyst, mixed for 3min, and poured into a dispensing tube as PDMS-OH / Ag conductive ink for printing. The designed parallel pattern was printed on the pre-stretched P(MEA-co-BA) substrate using a high-viscosity dispensing printer V-One. The dispensing needle was 27G (inner diameter 0.21mm, outer diameter 0.4mm), the parallel line length was 1-3mm, the lateral arrangement period was 0.85mm, the number of parallel lines was 25-60, the dispensing printing height was 0.2-0.4mm, and the printing speed was 20-30mm / min, which can be adjusted according to the final use requirements of the strain sensor. The thickness of the dispensing head needs to match the parameters such as the printing cycle, and the interval between adjacent patterns is reduced as much as possible to ensure that the adjacent patterns can contact after the pre-stretching is released. After printing, it is heated at 70°C for more than 30 minutes to cure. The obtained sample is as follows Figure 3 shown.
[0071] ⑤Chemical reduction gold plating
[0072] The printed sample is separated from the glass slide by dissolving the sacrificial layer underwater. After separation, the redundant part without printed pattern on the edge is cut off and immersed in the gold plating solution for replacement gold plating to improve the contact resistance of adjacent patterns after retraction and improve the stability of the strain sensor. The gold plating solution is an aqueous solution containing 1mM HAuCl4, 8.4mM Na2S2O3 and 8.4mM Na2SO3. After dissolving Na2S2O3 and Na2SO3 in water, high concentration HAuCl4 is added while stirring. After preparation, the sample is immersed in the solution at 70℃ for 2h, and then taken out and rinsed with plenty of water. Since the polymer substrate of the sensor has pressure-sensitive adhesive properties, its adhesiveness helps to fit the skin. It is stored on release paper for easy access. Figure 4 shown.
[0073] ⑥Packaging
[0074] The cut commercial gold-plated polyimide (PI) film was attached to both sides of the printed pattern as a conductor to obtain the final flexible strain sensor. Its microscopic morphology is as follows Figure 5 As shown, after pre-stretching and shrinkage, the distance between adjacent printed patterns is less than 20 μm. Due to the dense AgNWs network on the surface of the P(MEA-co-BA) polymer film, the retracted printed pattern can achieve stable electrical contact. From the enlarged SEM image, it can be seen that there is silver microflake powder added to the printing ink on the pattern surface, and the embedded AgNWs network can be seen on the bottom surface of the P(MEA-co-BA) film in the gaps between adjacent patterns.
[0075] The sensing performance of strain sensors is as follows Figure 6 As shown, including strain response curve and cyclic stability test, where GF = (ΔR / R0) / ε, is the relative change ΔR of the sensor resistance, divided by the initial resistance R0 when the strain is zero, and then divided by the strain amount ε, corresponding to the slope value in the response curve, characterizing the sensitivity of the sensor. It can be seen that the strain sensor has a very high sensitivity in a small strain range, and at the same time, it shows excellent electrical / mechanical stability in 2500 stretch-recovery cycle tests.
[0076] In summary, the present invention provides a flexible strain sensor and a method for preparing the same. Compared with conventional technologies, the main advantages of the flexible strain sensor of the present invention are:
[0077] ① Controllability of preparation. Compared with traditional crack-type strain sensors, the consistency and repeatability of the preparation process are difficult to guarantee because the crack formation process is random and uncontrollable. This experimental scheme is based on the pre-stretching-dispensing printing method, which transforms the uncontrollable crack-type path in the strain sensing mechanism into a controllable pattern path. During the preparation process, the pre-stretching ratio of the polymer substrate, the length, interval, cycle and range of the dispensing printing pattern can be adjusted, and the preparation process of the strain sensor is highly controllable.
[0078] ② Stability of sensing performance. Although the sensitivity of crack-type strain sensors is significantly improved, new cracks may be generated during the stretching-retraction process. At the same time, the retraction contact of micro / nanocracks during stretching recovery is uncontrollable, resulting in unstable sensing performance of strain sensors. As the number of stretching cycles increases, the initial resistance of the device often drifts upward. This experimental scheme transforms the generation and recovery of cracks into the contact and separation of adjacent printed patterns, and additionally introduces a chemical reduction gold plating method to improve the contact resistance of adjacent patterns. Since it does not involve the generation and recovery of cracks, the stability of the sensing performance is improved.
[0079] ③ Balance between sensing working range and sensitivity. In order to improve the sensitivity of the sensor, crack-type strain sensors are often designed to completely destroy the conductive circuit under a smaller strain range to increase the generation of micro / nanocracks and improve sensitivity, which limits their sensing working range. This experimental scheme is based on the retraction pattern prepared by pre-stretching-dispensing printing, the AgNWs network embedded on the surface, and the ionic conductor P (MEA-co-BA) at the bottom, which further increases the sensing working range while ensuring the sensitivity of the sensor.
[0080] The above content is a further detailed description of the present invention in combination with specific / preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, it can also make several substitutions or modifications to these described embodiments, and these substitutions or modifications should be regarded as belonging to the protection scope of the present invention. In the description of this specification, the description of the reference terms "an embodiment", "some embodiments", "preferred embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in combination with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily target the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In the absence of mutual contradiction, those skilled in the art can combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples. Although the embodiments of the present invention and their advantages have been described in detail, it should be understood that various changes, substitutions and modifications can be made herein without departing from the scope of protection of the patent application.
Claims
1. A flexible strain sensor, characterized in that: include: A polymer substrate, wherein the polymer substrate is composed of a copolymer P(MEA-co-BA) of 2-methoxyethyl acrylate (MEA) and 2-butyl acrylate (BA), and a silver nanowire (AgNWs) network is embedded on the surface; A conductive pattern, wherein the conductive pattern is printed on a pre-stretched polymer substrate by dispensing to form a parallel pattern structure; A chemical reduction gold plating layer is formed on the conductive pattern to improve contact resistance and enhance sensor stability; The gold-plated polyimide (PI) film is connected to the conductive pattern as a conductor to transmit electrical signals.
2. The flexible strain sensor according to claim 1, characterized in that: After pre-stretching and retraction, the spacing between adjacent printed patterns is no more than 20 μm, the length of the parallel lines is 1-3 mm, and the number of parallel lines is 25-60.
3. A method for preparing a flexible strain sensor, characterized in that: The following steps are involved: S1, preparing a polymer substrate composed of a copolymer of 2-methoxyethyl acrylate (MEA) and 2-butyl acrylate (BA) P(MEA-co-BA), and embedding a silver nanowire (AgNWs) network on the surface; S2, pre-stretching the polymer substrate to a predetermined degree and fixing it; S3, printing a conductive pattern on a pre-stretched polymer substrate by dispensing to form a parallel-arranged pattern structure; S4, performing chemical reduction gold plating on the conductive pattern to improve contact resistance and enhance sensor stability; S5. Connect the conductive pattern to the gold-plated polyimide (PI) film to form a conductive connection for transmitting electrical signals.
4. The method for preparing the flexible strain sensor according to claim 3, characterized in that: Step S1 includes preparing a glass slide interlayer coated with silver nanowires (AgNWs), specifically comprising: Add silver nanowire (AgNWs) ethanol dispersion dropwise onto a glass slide and evenly wet the entire surface of the glass slide; place the treated glass slide on a horizontally placed heating plate and heat and dry it for later use; After the surface of another glass slide was treated in an oxygen plasma cleaning machine, a dextran (molecular weight 40,000) aqueous solution was spin-coated and the residual water was evaporated by heating to form a water-soluble sacrificial layer.
5. The method for preparing the flexible strain sensor according to claim 3 or 4, characterized in that: In step S1, the preparation of the polymer substrate specifically includes: 2-Methoxyethyl acrylate (MEA) and 2-butyl acrylate (BA) were mixed at a molar ratio of 1:1; Add 0.1% polyethylene glycol diacrylate (PEGDA) relative to the total molar amount of MEA and BA; Add 1% 1-hydroxycyclohexylphenyl ketone (photoinitiator 184) relative to the total molar amount of MEA and BA; 0.1–2 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) was added as an ionic liquid to enhance the conductivity of the polymer; The resulting mixture was injected into a glass slide sandwich coated with an AgNWs layer and photo-initiated polymerization was achieved by ultraviolet light irradiation.
6. The method for preparing a flexible strain sensor according to any one of claims 3 to 5, characterized in that: In step S2, the polymer substrate is pre-stretched to a length of 140%-200%.
7. The method for preparing a flexible strain sensor according to any one of claims 3 to 6, characterized in that: In step S3, the conductive ink used for dispensing printing includes the following components: hydroxyl-terminated polydimethylsiloxane PDMS-OH; octamethylcyclotetrasiloxane D4; crosslinking agent 3-(2,3-epoxypropyloxy)propyltrimethoxysilane (GPTMS); silver microflake powder; dibutyltin dilaurate (DBTDL) as a catalyst.
8. The method for preparing a flexible strain sensor according to any one of claims 3 to 7, characterized in that: In step S3, the length of the parallel lines printed by glue dispensing is 1-3mm, the horizontal arrangement period is 0.85mm, the number of parallel lines is 25-60, the height of glue dispensing printing is 0.2-0.4mm, and the printing speed is 20-30mm / min to ensure that adjacent patterns can contact after pre-stretching is released, and they are heated at 70°C for more than 30 minutes after printing to cure; the spacing between adjacent printed patterns after pre-stretching and retraction is no more than 20μm.
9. The method for preparing a flexible strain sensor according to any one of claims 3 to 8, characterized in that: In step S4, the gold plating solution used in the chemical reduction gold plating contains HAuCl4, Na2S2O3 and Na2SO3.
10. The method for preparing the flexible strain sensor according to claim 9, characterized in that: In step S4, the sample is immersed in the solution and reacted at 70° C. for 2 hours.
Citation Information
Patent Citations
Metallic film flexible strain sensor and preparation method therefor
CN105627905A
Flexible strain sensor based on regular micron crack array structure and preparation method thereof
CN108444377A
Method for preparing flexible electronic device with high conductivity, self repairing and stretchability
CN108877996A
Amorphous carbon-based flexible sensor based on crack fold structure and preparation method thereof
CN113720255A
Preparation method of flexible strain sensor based on AgNWs-MXene
CN114963962A